SIFAT FISIKOKIMIA DAN SENSORIS INSTANT STARCH NOODLE PATI AREN YANG DISUBSTITUSI DENGAN PATI TAPIOKA - Nur Alam (Agroland: Jurnal Ilmu-ilmu Pertanian, 2008)
The research aimed to identify the physico-chemical and sensory characteristics of aren instant starch noodle (ISN) substituted with 0, 5, 10, 15, 20, and 25% of tapioca starch.  The physicochemical and sensory characteristics observed were gelatinization level, water content, white degree, cooking rate, cooking loss, tensile strength, elongation, texture, performance, aroma, taste and viscosity.  Corn ISN was used as a comparison. The research results showed that the percentage of the tapioca starch that could substitute the aren starch was in the ranges of 5 – 20%.  Substituting with 20% tapioca starch could yield ISN most similar to the corn ISN in which physicochemical and sensory characteristics were acceptable to consumers.  However, the water content of the ISN resulted from the research still higher than that of standard category, therefore the time length for drying need to be prolonged.